Liaison psychiatry practitioners' views on accessing aftercare and psychological therapies for patients who present to hospital following self-harm: multi-site interview study. Issue 2 (20th March 2023) - Quinlivan, Leah; Gorman, Louise; Marks, Stephen; Monaghan, Elizabeth; Asmal, Sadika; Webb, Roger T.; Kapur, Nav
Abstract : Background: Timely provision of aftercare following self-harm may reduce risks of repetition and premature death, but existing services are frequently reported as being inadequate. Aims: To explore barriers and facilitators to accessing aftercare and psychological therapies for patients presenting to hospital following self-harm, from the perspective of liaison psychiatry practitioners. Method: Between March 2019 and December 2020, we interviewed 51 staff members across 32 liaison psychiatry services in England. We used thematic analyses to interpret the interview data. Results: Barriers to accessing services may heighten risk of further self-harm for patients and burnout for staff. Barriers included: perceived risk, exclusionary thresholds, long waiting times, siloed working and bureaucracy. Strategies to increase access to aftercare included: (a) improving assessments and care plans via input from skilled staff working in multidisciplinary teams (e.g. including social workers and clinical psychologists); (b) supporting staff to focus on assessments as therapeutic intervention; (c) probing boundaries and involving senior staff to negotiate risk and advocate for patients; and (d) building relationships and integration across services. Conclusions: Our findings highlight practitioners' views on barriers to accessing aftercare and strategies to circumvent some of these impediments. Provision of aftercare and psychological therapies as part of the liaison psychiatry service were deemed as an essential mechanism for optimising patient safety and experience and staff well-being. To close treatment gaps and reduce inequalities, it is important to work closely with staff and patients, learn from experiences of good practice and implement change more widely across services.